Inhibition of Platelet Adhesion to Fibrin(ogen) in Flowing Whole Blood by Arg-Gly-Asp and Fibrinogen γ-Chain Carboxy Terminal Peptides - Hantgan, Roy R; Endenburg, Silvia C; Cavero, I; Marguerie, Gérard; Uzan, André; Sixma, Jan J; de Groot, Philip G (Thrombosis and Haemostasis, 1992)
We have employed synthetic peptides with sequences corresponding to the integrin receptor-recognition regions of fibrinogen as inhibitors of platelet aggregation and adhesion to fibrinogen-and fibrin-coated surfaces in flowing whole blood, using a rectangular perfusion chamber at wall shear rates of 300 s–1 and 1,300 s–1. D-RGDW caused substantial inhibition of platelet aggregation and adhesion to fibrinogen and fibrin at both shear rates, although it was least effective at blocking platelet adhesion to fibrin at 300 s–1. RGDS was a weaker inhibitor, and produced a biphasic dose-response curve; SDRG was inactive. HHLGGAK-QAGDV partially inhibited platelet aggregation and adhesion to fibrin(ogen) at both shear rates. These results support the identification of an RGD-specific receptor, most likely the platelet integrin glycoprotein IIb: III a, as the primary receptor responsible for platelet: fibrin(ogen) adhesive interactions under flow conditions, and indicate that platelet adhesion to surface bound fibrin(ogen) is stabilized by multivalent receptor-ligand contacts.